Capital and Labor: The Factor Income Composition of Top Incomes in the United States, 1962–2006 - Atkinson, Anthony B.; Lakner, Christoph (The Review of Economics and Statistics, 2021)
This paper finds that capital and labor incomes in the United States have become more closely associated since the 1980s. This has contributed to the well-known increase in the top 1% share of total income, exacerbating rising inequality in capital incomes and earnings. We show that the trend in the association is U-shaped as the recent increase contrasts with a tendency toward a weakening association until the 1980s. The paper, using data derived from tax records, studies the asymmetries in the association and tests for robustness to alternative income definitions, including the role of income from closely held businesses at the top.